2010
DOI: 10.3892/ijmm_00000480
|View full text |Cite
|
Sign up to set email alerts
|

Selective aldosterone blocker ameliorates the progression of non-alcoholic steatohepatitis in rats

Abstract: Abstract. Although non-alcoholic steatohepatitis (NASH) may progress to cirrhosis and hepatocellular carcinoma (HCC), no effective therapeutic modalities have been fully established yet. Recent studies have shown that the reninangiotensin-aldosterone-system plays an important role in NASH. The aim of our current study was to elucidate the effects of aldosterone (Ald) inhibition on the progression of NASH. In the choline-deficient L-amino acid-defined dietinduced rat NASH model, the effects of a clinically used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Together, these treatment results indicated that aldosterone plays a pivotal role in the progression of NAFLD. 27 In subgroup analysis, our study found that the risk of NAFLD was associated with a higher PAC in hypertensive patients without diabetes than in those with diabetes. The reason underlying the association was the number of diabetes patients who accepted antidiabetic agents, including metformin, insulin, pioglitazone, glucagon-like peptide-1 agonists, sodium-glucose co-transporter-2, and dipeptidyl peptidase-4 inhibitors, which had a beneficial effect on the prevention of NAFLD.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Together, these treatment results indicated that aldosterone plays a pivotal role in the progression of NAFLD. 27 In subgroup analysis, our study found that the risk of NAFLD was associated with a higher PAC in hypertensive patients without diabetes than in those with diabetes. The reason underlying the association was the number of diabetes patients who accepted antidiabetic agents, including metformin, insulin, pioglitazone, glucagon-like peptide-1 agonists, sodium-glucose co-transporter-2, and dipeptidyl peptidase-4 inhibitors, which had a beneficial effect on the prevention of NAFLD.…”
Section: Discussionmentioning
confidence: 59%
“… 26 A selective aldosterone blocker (SAB) has been shown to attenuate fibrogenesis and suppress activated hepatic stellate cells in other studies. 27 However, one study suggests that aldosterone excess may not be correlated with the development of fatty liver disease in a mouse model fed a high-fat diet. 28 Nevertheless, there is a need for further investigation into the association between high plasma aldosterone concentrations (PAC) and NAFLD in hypertensive patients, given the controversial findings.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a negative correlation between plasma aldosterone and HDL cholesterol levels was reported in essential hypertensive patients with obesity and insulin resistance early on that was not found in later studies (18,23). After the correction of excess aldosterone, either by surgery in patients with aldosteronoma or medication in those with hyperplasia, significant improvements in the metabolic parameters were observed (24)(25)(26). Consistent with this finding, our study also showed that metabolic disorders, especially NAFLD, diabetes and dyslipidemia, were more prevalent in PA patients than in non-PA patients.…”
Section: Discussionmentioning
confidence: 94%
“…Other major effects of the hormone include the induction of proinflammatory activity, which leads to the progressive fibrotic damage of the target organs, heart and kidney. Blocking the aldosterone receptor, therefore, represents an important pharmacological strategy to avoid the clinical conditions arising from NASH [ 98 , 99 ] and CKD [ 100 , 101 , 102 ]. Apararenone (MT-3995) [ 103 ] is a nonsteroidal antimineralocorticoid which is under development for the treatment of diabetic nephropathies and NASH ( Table 1 ).…”
Section: Common Drug Pipelines For Nafld/nash and Diabetic Nephropmentioning
confidence: 99%